2012
DOI: 10.1002/jctb.3693
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of magnetic beads containing aminated fibrous surfaces for removal of Reactive Green 19 dye: kinetics and thermodynamic parameters

Abstract: BACKGROUND: Poly(HEMA-co-MMA) beads were prepared from 2-hydroxyethyl-methacrylate (HEMA) and methylmethacrylate (MMA) in the presence of FeCl 3 . Thermal co-precipitation of Fe(III) ions containing beads with Fe(II) ions was carried out under alkaline conditions. The magnetic beads were grafted with poly(glycidylmethacrylate; p(GMA)), and the epoxy groups of the grafted p(GMA) brushes were converted into amino groups by reaction with ammonia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 41 publications
1
24
0
Order By: Relevance
“…Over the years, magnetic nanoparticles have been employed by researchers in the field of adsorption/biosorption for separation of pollutants from polluted‐water . The utilization of these materials makes the separation of both the adsorbent and the adsorbate much easier from water.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the years, magnetic nanoparticles have been employed by researchers in the field of adsorption/biosorption for separation of pollutants from polluted‐water . The utilization of these materials makes the separation of both the adsorbent and the adsorbate much easier from water.…”
Section: Introductionmentioning
confidence: 99%
“…8,10,11 Over the years, magnetic nanoparticles have been employed by researchers in the field of adsorption/biosorption for separation of pollutants from polluted-water. 7,8,12 The utilization of these materials makes the separation of both the adsorbent and the adsorbate much easier from water. Hence, the water does not need to be filtered or centrifuged after the adsorption process, which is considered a critical advantage.…”
Section: Introductionmentioning
confidence: 99%
“…The observed deviation may be attributed to the weakening of the attractive forces between adsorbent and adsorbate molecules or the possible alteration of active sites by increasing temperature. Moreover, the value of Langmuir constant (b) was observed to decrease with increase in temperature, which indicated that the affinity between adsorbent and adsorbate decreased with increase in temperature [9,43].…”
Section: Optimization Of Different Reaction Parametersmentioning
confidence: 99%
“…Various treatment processes such as ozonation , coagulation , ultrafiltration , oxidation , photocatalytic degradation , and adsorption are applied for dye removal from wastewater, but adsorption is considered as the most efficient method for the removal of dyes from wastewater . In the recent years, extensive research has been undertaken to develop alternative and cost‐effective adsorbents .…”
Section: Introductionmentioning
confidence: 99%
“…To prevent dye discharge and contamination, the removal of dyes from aqueous environments by various methods such as advance oxidation , biodegradation , membrane filtration and adsorption has been reported. Many adsorbents have been tested for their potential to lower dye concentrations from aqueous solutions, such as acrylic acid containing crosslinked vinyl benzylchloride beads , carbon, modified clay , chitosan, poly(propylene imine) dendrimer, magnetic nanocomposite hydrogels and others . The adsorption process is generally recommended for the removal of dyes because of its easy handling, high efficiency, regenerability, availability of different adsorbents and cost effectiveness.…”
Section: Introductionmentioning
confidence: 99%